Notes on feminine contemporary experiences of migration and work - Lemme Ribeiro, Clara (Geografares, 2019)
Over the last years, the feminization of migrations has been considered one of the main social trends of the 21st century. The present paper investigates this process, underlining possible connections with social reproduction as a whole, through the analysis of Bolivian female migration trajectories. Feminine migratory experiences can be understood as a concrete content of the contemporary crisis of capital reproduction that simultaneously unfolds as a crisis of labor and reproduction.
Keywords: feminization of migrations; labor crisis; Bolivian migration; São Paulo, Brazil